IMPLEMENTASI MANAJEMEN PENDIDIKAN BERBASIS SYARIAH DI STAI AL-HIDAYAH BOGOR - Dahlinar Dahlinar; Wahyudin Nur Nasution; Afrahul Fadhila Daulay (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
Islam is the perfect religion that regulates all aspects of human life, including aspects of education. Education is one of the essential needs of man, because through education, people will be able to develop their potentials towards a better life. In the conception of Islam, the main function of educational institution is as a medium of education realization in order to realize servitude to Allah and to develop any talents or potential people in accordance with their respective trends. In the Islamic view, everything must be done neatly, correctly, orderly and organized. The process must be followed properly. Something should not be done carelessly. In this case, the STAI Al-Hidayah Bogor set the vision and mission as an institution of higher education which is based on the concept and practice of sharia in its management which includes kinds of activities, like planning, supervision, organization, evaluation, and so on. This articel is striving to explain the concept and its implementation of education management sharia-based in accordance with studies at STAI Al-Hidayah Bogor. Through this paper is expected to provide knowledge about the concept and model of education management approach to the implementation of sharia in Islamic educational institutions. This study is adescriptive qualitative research methods. The writer restricts the research objects in to the concept and implementation of Islamic-based education management in STAI Al-Hidayah, obtained through a reviewof the relevant reference works of writers before, and observations and interview sconcerning management officers of STAI Al-Hidayah Bogor. The sources of secondary data obtained from books, papers or article general managementand management education that Islamic approach. In-depth study has concluded important basic concepts, namely the concept of implementing Sharia-Based Management in STAI Al-Hidayah Bogor, implemented starting from the planning, organizing, directing, monitoring and evaluation, through the official rules in the regulation of the management of STAI Al-Hidayah has based and adapted to Islamic rule, although it is still much that needs to be refined in the details of its implementation. The writer invites, the Muslim community should give greater attention to the management of educationat every step of its implementation in order to remain committed in the corridor and Islamic guidance, as many practices exemplified by the Prophet Muhammad Kata kunci: manajemen pendidikan, syar’ah, STAI Al-Hidayah Bogor